1999
DOI: 10.1055/s-2008-1072304
|View full text |Cite
|
Sign up to set email alerts
|

19-Year Follow-Up of Fetal Myelomeningocele Brought to Term

Abstract: We conducted a 19-year follow-up study of 223 infants with myelomeningocele born by cephalic presentation, 68 born by pre-rupture of amniotic membranes cesarean section (PRAM C/S) and 155 born vaginally to determine outcome. We recorded radiographic level as the last intact vertebral arch at the cephalad end of the spinal defect from standard AP films of the spine. Protrusions of the lesions dorsal to the back were obtained from medical records or parental recall. Subsequent spinal cord abnormalities (hydromye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 6 publications
0
12
0
Order By: Relevance
“…Our large study of fetuses with myelomeningocele suggests that cesarean section delivery improves motor outcomes and may decrease the likelihood of infection and prevent brain damage from bleeding (Luthy et al, 1991). We now recommend cesarean section delivery before rupture of amniotic membranes for fetuses with myelomeningocele meeting the following criteria: 1) lesion protruding more than 1 cm beyond the surface of the back; 2) intact knee movement; and 3) absence of other severe, untreatable malformations or chromosomal anomalies (Liu et al, 1999). Several smaller studies have not confirmed a positive effect for pre-labor cesarean section; however, these studies did not take into account the selection criteria above (Merrill et al, 1998;Owen, 1998;Lewis et al, 2004).…”
Section: Pregnancy Managementmentioning
confidence: 89%
“…Our large study of fetuses with myelomeningocele suggests that cesarean section delivery improves motor outcomes and may decrease the likelihood of infection and prevent brain damage from bleeding (Luthy et al, 1991). We now recommend cesarean section delivery before rupture of amniotic membranes for fetuses with myelomeningocele meeting the following criteria: 1) lesion protruding more than 1 cm beyond the surface of the back; 2) intact knee movement; and 3) absence of other severe, untreatable malformations or chromosomal anomalies (Liu et al, 1999). Several smaller studies have not confirmed a positive effect for pre-labor cesarean section; however, these studies did not take into account the selection criteria above (Merrill et al, 1998;Owen, 1998;Lewis et al, 2004).…”
Section: Pregnancy Managementmentioning
confidence: 89%
“…Spreadsheet software is widely used in the business community for data manipulation, calculation and presentation. Previous studies suggest Excel is a valid and reliable business tool (Brown, 1999;Liu, Shurtleff, Ellenbogen, Loeser, & Kropp, 1999;Walter, 1999). Excel® greatly simplified the repetitive calculations associated with rate analysis.…”
Section: Spreadsheet Softwarementioning
confidence: 99%
“…It has the potential of being useful in distinguishing between toxicity from late gestational amniotic fluid to exposed nerves 2 and the trauma of delivery. [3][4][5] To do so would require comparing patients with prenatally repaired myelomeningocele lesions to children with myelomeningocele and functional leg muscles, and a sac protruding 2cm or more beyond the dorsal plane of the back prior to rupture of the amniotic membranes. 4,5 Muscle ultrasound density would be more useful in predicting future lower extremity function in the newborn with myelomeningocele if used to more accurately display individual muscle density over time.…”
mentioning
confidence: 99%
“…[3][4][5] To do so would require comparing patients with prenatally repaired myelomeningocele lesions to children with myelomeningocele and functional leg muscles, and a sac protruding 2cm or more beyond the dorsal plane of the back prior to rupture of the amniotic membranes. 4,5 Muscle ultrasound density would be more useful in predicting future lower extremity function in the newborn with myelomeningocele if used to more accurately display individual muscle density over time. 6,7 Fetal endoscopic myelomeningocele closure, the second technological advance, is listed in both the title and conclusion of the article.…”
mentioning
confidence: 99%
See 1 more Smart Citation